Study of Fabrication, Testing and Characterization of Al/TiC Metal Matrix Composites through different Processing Techniques. (2018) - Pandey, Utkarsh; Purohit, Rajesh; Agarwal, Pankaj; Kumar Singh, Swadesh
Abstract: The various techniques for the of fabrication of Al/TiC metal matrix composites such as powder metallurgy, friction stir processing, flux assisted synthesis, accumulative roll bonding and most popular In-situ etc. have been studied. Ultrasonic assisted stir casting process or in other words vortex method via liquid metallurgy method has evolved as economical and simple technique to fabricate metal matrix composites in the recent years. There are very few literature available on fabrication of Al/TiC metal matrix composites through Ex-situ method via stir casting processing. The objective of Metal matrix composites (MMC) focused primarily on improved specific strength, micro hardness, high temperature application, low density, and high wear resistance. Al/TiC are potential materials for aircraft, defence and aerospace applications. The aim of this paper is to study the current research and development in aluminium alloy 6061-titanium carbide based composites by different processing techniques with special focus on in situ and ex-situ stir casting route. Very limited studies have been reported on TiC particulates synthesized with Al matrix composites. TiC particulates reinforced composites are well featured by the particulate-matrix bonding and interface studies particularly with aluminium and proved to be a potential reinforcement for improved mechanical properties in Al/TiC Composites especially for micro hardness, wear and compressive strength.